2015
DOI: 10.1093/cid/civ951
|View full text |Cite
|
Sign up to set email alerts
|

Viral Shedding and Antibody Response in 37 Patients With Middle East Respiratory Syndrome Coronavirus Infection

Abstract: The timing and intensity of respiratory viral shedding in patients with MERS closely matches that of those with severe acute respiratory syndrome. Blood viral RNA does not seem to be infectious. Extrapulmonary loci of virus replication seem possible. Neutralizing antibodies do not suffice to clear the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
385
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(420 citation statements)
references
References 34 publications
22
385
1
12
Order By: Relevance
“…Whether this viral RNA represented an extrapulmonary infection is not clear, since MERS-CoV neutralising antibody was detected in the serum at the same time in some patients. 49 Pathological changes in the lungs include evidence of focal haemorrhagic necrotising pneumonia with exudative diffuse alveolar damage, indistinguishable from findings detected in severe pneumonia caused by other viral agents.…”
Section: Pathogenesis and Pathologymentioning
confidence: 96%
See 1 more Smart Citation
“…Whether this viral RNA represented an extrapulmonary infection is not clear, since MERS-CoV neutralising antibody was detected in the serum at the same time in some patients. 49 Pathological changes in the lungs include evidence of focal haemorrhagic necrotising pneumonia with exudative diffuse alveolar damage, indistinguishable from findings detected in severe pneumonia caused by other viral agents.…”
Section: Pathogenesis and Pathologymentioning
confidence: 96%
“…57 T-cell and antibody responses were reliably detected 2-3 weeks after diagnosis, although they were detected earlier in some patients. 49,57 Studies of MERS survivors showed that MERS-CoV-specific antibody responses tended to be lower and transient in patients with mild or subclinical disease when compared with patients with severe disease, in whom MERS-CoV-specific antibody responses were detected for at least 2 years. [57][58][59][60] In contrast, T-cell responses were detected in all MERS survivors for at least 2 years.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 99%
“…Reasons for low sensitivity of PCR may include insensitive nucleic acid detection methods and variations in the accuracies of different tests, low initial viral load or improper clinical sampling [4]. An additional reason may be that lower respiratory samples may be better than upper respiratory samples, as is the cases with MERS-CoV [5] [6].…”
mentioning
confidence: 99%
“…15 In addition to that, the virus has been easily isolated from samples of patients' lower respiratory tract (tracheal aspirates, sputum, or bronchoalveolar lavage fluid), and this shedding might occur for numerous weeks and exceed by load that from other routes of exit (stool, serum). 16 The incubation period for this disease ranges from two to sixteen days, with a mean of five to six days. Also, after studying the natural history of the disease, the communicability period has been established at 13 to 14 days after an individual becomes symptomatic.…”
Section: The Agentmentioning
confidence: 99%